Kisah Al-Qur’an dan Ayat-ayat yang Memiliki Kemiripan Susunan Kata: Sebuah Tinjauan Sintaksis Arab - Holilulloh, Andi; Huda, M. Nurul (Universitas Negeri Jakarta, 2023)
The method of understanding the story of the Quran using a historical approach is that in several verses it has experienced deadlocks in the editorials of similar verses. Thus, a stylistic approach that focuses on the analysis of Arabic syntax is needed to understand these verses. This study aims to answer questions about the interpretation of stories in the verses of the Quran that have the same word order. The method used in this study is content analysis with a stylistic approach at the syntactic level. The primary data sources used are stories in the verses of the Quran that have similar wording, while the secondary sources used are related and relevant to the research topic. The results of this study indicate that the verses of the Quran with similar wording do not always refer to the same events. One element of the story can be described in various versions according to the intent and purpose of the story. This article can contribute to understanding the story in the verses of the Quran. Apart from the historical approach, a stylistic approach can also be helpful, especially at the level of Arabic syntax.